Potential of Biochar to Reduce Greenhouse Gas Emissions and Increase Nitrogen Use Efficiency in Boreal Arable Soils in the Long-Term - Kalu, Subin; Kulmala, Liisa; Zrim, Jure; Peltokangas, Kenneth; Tammeorg, Priit; Rasa, Kimmo; Kitzler, Barbara; Pihlatie, Mari; Karhu, Kristiina (Frontiers in Environmental Science, 2022)
Biochars have potential to provide agricultural and environmental benefits such as increasing soil carbon sequestration, crop yield, and soil fertility while reducing greenhouse gas (GHG) emissions and nitrogen leaching. However, whether these effects will sustain for the long-term is still unknown. Moreover, these effects were observed mostly in highly weathered (sub-) tropical soils with low pH and soil organic carbon (SOC). The soils in northern colder boreal regions have typically higher SOC and undergo continuous freeze-thaw cycles. Therefore, effects of biochars in these regions may be different from those observed in other climates. However, only a few biochar studies were conducted in boreal regions. We aimed to assess the long-term effects of biochars on GHG emissions, yield-normalized non-CO2 GHG emissions (GHGI), and N dynamics in boreal soils. For this, we collected data from four existing Finnish biochar field experiments during 2018 growing season. The experiments were Jokioinen (Stagnosol), Qvidja (Cambisol), Viikki-1 (Stagnosol), and Viikki-2 (Umbrisol), where biochars were applied, two, two, eight, and seven years before, respectively. The GHG emissions, crop yield, soil mineral N, and microbial biomass were measured from all fields, whereas, additional measurements of plant N contents and N leaching were conducted in Qvidja. Biochars increased CO2 efflux in Qvidja and Viikki-2, whereas, there were no statistically significant effects of biochars on the fluxes of N2O or CH4, but in Qvidja, biochars tended to reduce N2O fluxes at the peak emission points. The tendency of biochars to reduce N2O emissions seemed higher in soils with higher silt content and lower initial soil carbon. We demonstrated the long-term effects of biochar on increased crop yield by 65% and reduced GHGI by 43% in Viikki-2. In Qvidja, the significant increment of plant biomass, plant N uptake, nitrogen use efficiency, and crop yield, and reduction of NO3−–N leaching by the spruce biochar is attributed to its ability to retain NO3−–N, which could be linked to its significantly higher specific surface area. The ability of the spruce biochar to retain soil NO3−–N and hence to reduce N losses, has implications for sustainable management of N fertilization.